Safety and Tolerability of Intra-Articular Injection of Adipose-Derived Mesenchymal Stem Cells GXCPC1 in 11 Subjects With Knee Osteoarthritis: A Nonrandomized Pilot Study Without a Control Arm - Chen, Cheng-Fong; Chen, Yi-Chung; Fu, Yu-Show; Tsai, Shang-Wen; Wu, Po-Kuei; Chen, Chao-Ming; Chen, Wei-Ming; Wu, Hung-Ta Hondar; Lee, Chia-Hsin; Chang, Chao-Liang; Lin, Po-Cheng; Kao, Yong-Cheng; et al. (Cell transplantation, 2024)
The current study aimed to determine the safety profile of intra-articular-injected allogeneic adipose-derived mesenchymal stem cells (ADSCs) GXCPC1 in subjects with knee osteoarthritis (OA) and its preliminary efficacy outcome. The 3 + 3 phase I study was designed with two dose-escalation cohorts: low dose (6.7 × 106 GXCPC1, N = 5) and high dose (4 × 107 GXCPC1, N = 6). The primary endpoint was safety, which was evaluated by recording adverse events throughout the trial; the secondary endpoints included total, pain, stiffness, and function subscales of the Western Ontario and McMaster Universities Arthritis Index (WOMAC), Visual Analogue Scale (VAS) for pain, and 12-Item Short Form (SF-12) health survey questionnaire. The GXCPC1 treatment was found to be safe after 1 year of follow-up with no treatment-related severe adverse events observed. When compared to baseline, subjects in both the low- and high-dose cohorts demonstrated improving trends in pain and knee function after receiving GXCPC1 treatment. Generally, the net change in pain (95% confidence interval (CI) = −7.773 to −2.561t at 12 weeks compared to baseline) and knee function (95% CI = −24.297 to −10.036t at 12 weeks compared to baseline) was better in subjects receiving high-dose GXCPC1. Although this study included a limited number of subjects without a placebo arm, it showed that the intra-articular injection of ADSCs was safe and well-tolerated in subjects with therapeutic alternatives to treat knee OA. However, a larger scale study with an appropriate control would be necessary for clinical efficacy in the following study.